(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article delves into the multifaceted functions of code-switching, a linguistic phenomenon characterized by the alternating use of two or more languages within a single conversation. By exploring the diverse dimensions of code-switching, including identity expression, group solidarity, semantic precision, social marking, creativity, and adaptation to context.